2015
DOI: 10.1002/hed.23497
|View full text |Cite
|
Sign up to set email alerts
|

Inherently poor survival of elderly patients with nasopharyngeal carcinoma

Abstract: The elderly patients with NPC may inherently predict poor outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 18 publications
1
33
1
Order By: Relevance
“…One of these is the effects of NPC on older patients. A few large studies of patients in Asia have found that older people with NPC have inferior outcomes . However, data for patients in other regions are less comprehensive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these is the effects of NPC on older patients. A few large studies of patients in Asia have found that older people with NPC have inferior outcomes . However, data for patients in other regions are less comprehensive.…”
Section: Introductionmentioning
confidence: 99%
“…A few large studies of patients in Asia have found that older people with NPC have inferior outcomes. [27][28][29][30] However, data for patients in other regions are less comprehensive. Given that the worldwide population is ageing, 31 additional research is needed to delineate other aspects of NPC in the elderly.…”
mentioning
confidence: 99%
“…excellent outcomes, similar to patients with lower scores, it is reasonable to infer that the original NRS2002 scale may not provide adequate nutritional risk stratification in NPC. Therefore, based on previous studies,12,24,25 we made some modifications to the age and weight loss criteria to establish a revised NRS2002 scale. ROC curve analysis revealed that the revised NRS2002 scale achieved the best power in risk stratification than the original NRS2002 and regrouping scales for all end-points.…”
mentioning
confidence: 99%
“…For example, the Epstein‐Barr virus (EBV) plasma titre is a well‐known independent prognostic factor in NPC . In addition, a family history of NPC, blood type A, diabetes mellitus, age > 65 years and a decreased albumin‐to‐globulin ratio is also associated with inferior outcomes. Thus, identification of new prognostic factors is important to improve the prediction of prognosis.…”
Section: Introductionmentioning
confidence: 99%